THE DE-OFFSHORE-ISATION OF THE RUSSIAN ECONOMY AS A FACTOR IN THE RECOVERY OF THE ECONOMIC SOVEREIGNTY OF THE COUNTRY - Alla L. Dykhova; Elena V. Ilinich (Статистика и экономика, 2016)
This article is devoted to problems of offshorization of the Russian economy andthe development of effective antioffshore policy aimed at restoring economic sovereignty of the country. The article examinesthe main causes of offshorization Russian business and the threat of economic security-related offshorization economy, and discusses the main directions of the development of a comprehensive antioffshore policy.